Doing science :design, analysis, and communication of scientific research / (Acc. 4687) design, analysis, and communication of scientific research - Valiela, Ivan. (Oxford ; New York : Oxford University Press, 2009)
Covers each stage of research, from formulating questions and gathering data to developing experiments and analyzing results and finally to the many ways for presenting results. --from publisher description
Keywords: Science; Communication in science; Technical writing